PENTINGNYA PAPAN NAMA JALAN UNTUK MENINGKATAN AKSESIBILITAS, ESTETIKA DAN FUNGSI DI DESA PARPAREAN IV - Tarigan, Enina Putri Aurora; Daeli, Perlita Fa’omasi; Sihotang, Rouli Angelina; Zega, Albert Kristian; Zalukhu, Marsefen Eka Wijaya (Merwinspy Publisher, 2025)
Road signage is one of the most important efforts in improving accessibility and navigation systems in an area, especially in rural areas that often do not have a clear road naming system. Parparean IV Village, Porsea Sub-district, Toba Regency, has an adequate road network with many small roads and alleys that are interconnected. However, the lack of street signage in this village causes difficulties in orientation and location finding, both for local communities and visiting migrants. To overcome these problems, this street signage program was implemented as part of HKBP Nommensen University Medan's Community Service and Practice Course (KPPM). This program aims to create a more structured street naming system to improve ease of access for the community and support the smooth running of social and economic activities. With clear and standardized street signage, it is hoped that connectivity between areas in Parparean IV Village will improve, so that various sectors, including trade, education and public services, can be further developed. In addition to providing practical benefits, the program also contributes to raising community awareness of the importance of road naming systems as part of village infrastructure development. The success of this program can serve as an example for other villages facing similar problems, as well as a first step in creating a more organized geographic information system to support sustainable village development.